AL-TSUNAIYYAH AL- TSAQAFIYYAH LADAY MUHADIRI AL-LUGAH AL-‘ARABIYYAH FI AL-JAMI‘AT AL-ISLAMIYYAH AL-HUKUMIYYAH FI JAWA AL-SYARQIYYAH - Rudisunhaji, Muhamad Asngad; Kojin, Kojin; Nurcholis, Ahmad; Machmudah, Umi (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2020)
This paper attempted to investigate the trends or cultural attitudes of Arabic lecturers of East Java’s State Islamic Universities (PTAIN) in using Arabic. To this end, the present study used a quantitative approach The results show that the directive utterances used by Arabic language lecturers at East Java’s PTAIN tend to take the form of direct speech acts through certain language politeness features. Besides, the hierarchy of the directive politeness speech in Arabic and Indonesian shared a similar degree of illocution. However, there is no significant difference between the hierarchy of directive politeness speech in Arabic, Indonesian, and Javanese perceived by the Arabic language teachers based on the Chi-square statistics test with α = 0.05. Consequently, they tend to use non-Arabic socio-cultural norms in expressing various directive utterances in Arabic.